PENGHITUNG JUMLAH WAJAH BERDASARKAN SISTEM DETEKSI WAJAH MENGGUNAKAN METODE VIOLA JONES - Ainun Nirwanto, Ahmad; Winarno, Edy (Information Technology and Telematics, 2018)
Abstark Face detection is widely used in many digital image processing experiments as a basis for recognizing and tracing faces. In this study built face detection system to be used to count the number of faces in an image. But the main problem that sometimes arises in the face detection method is in between, the less illumination in an image. With this method used in this system using viola jones method because it can reduce errors in face detection, viola jones method has several stages of processing that is Haar-Like Feature (haar feature), Integral Image, AdaBoost Learning, Cascade classifier, image input using an image and detected to count the number of faces contained in a photo. The test is done with 40 pieces of data. The test results show the accuracy of face detection rate of 93,4%